Respuesta :
Answer:
[tex]a+\sqrt{a-1}[/tex]
Step-by-step explanation:
The conjugate of an expression of the form:
[tex]z=a+b[/tex] (1)
is another expression of the form:
[tex]z=a-b[/tex] (2)
In the same way, if your expression is [tex]z=a-b[/tex], the conjugate is [tex]z=a+b[/tex].
You have the following expression:
[tex]a-\sqrt{a-1}[/tex]
by comparing with the equations (1) and (2) you can take a=a and b=√a-1. Thus, you have the expression z = a - b. The conjugate is z = a + b. Then, you can conclude that the conjugate is:
[tex]a+b=a+\sqrt{a-1}[/tex]
Answer:
the conjugate of [tex]a -\sqrt{a-1} \ = a + \sqrt{a -1}[/tex]
Step-by-step explanation:
Given;
[tex]a - \sqrt{a-1}[/tex]
Conjugate of [tex]a -\sqrt{x} \ \ \ is \ \ a \ + \ \sqrt{x}[/tex]
let (a - 1) = x
a - √x = a + √x
∴ [tex]a -\sqrt{a-1} \ = a + \sqrt{a -1}[/tex]
Therefore, the conjugate of [tex]a -\sqrt{a-1} \ = a + \sqrt{a -1}[/tex]
Check
[tex](a -\sqrt{a-1}) *(a+\sqrt{a-1} ) = a^2 + \ a\sqrt{a-1}\ - \ a\sqrt{a-1} - (a-1)\\\\(a -\sqrt{a-1}) *(a+\sqrt{a-1} ) = a^2 - (a-1)\\\\(a -\sqrt{a-1}) *(a+\sqrt{a-1} ) = a^2 -a+1[/tex]
The result is a rational number, hence [tex]a + \sqrt{a-1} \ \ is \ \ conjugate \ of \ \ a -\sqrt{a-1}[/tex]